Preparation method and application of BYD hydrogenation catalyst
In the process of preparing butyndiol with butyndiol, a fixed bed hydrogenation catalyst with the alloy core, the central active layer and the surface hydrogen storage layer is used to solve the problems of high reaction pressure, insufficient conversion and selectivity in the prior art, and efficient hydrogenation reaction at lower pressure is achieved, reducing production costs.
Patent Information
- Application Number
- CN202510000334.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
In the process of hydrogenation of butyndecyl glycol, the reaction pressure is high, the equipment investment is large, and the conversion rate and selectivity are insufficient, resulting in increased production of by-products and high process costs.
A fixed-bed hydrogenation catalyst including the alloy core, the middle active layer and the surface hydrogen storage layer is used to form a catalyst with high hydrogen absorption properties through the preparation of the nickel-aluminum alloy core, activation treatment and coating of the hydrogen storage solid solution.
The high selectivity of butylene glycol and the high conversion rate of butyndecyl glycol are achieved at lower reaction pressures (5-10MPa), reducing side reaction generation, reducing production costs and improving economic benefits.
Smart Images

Figure CN119794339A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogenation catalysts and preparation thereof, and in particular relates to a preparation method and application of a high-efficiency hydrogenation catalyst for preparing butanediol from butynediol. Background Art
[0002] 1,4-Butanediol (BDO) is an important organic synthesis intermediate with wide applications and large market demand. Its downstream products include polytetramethylene glycol ether (PTMEG), polybutylene terephthalate (PBT), tetrahydrofuran (THF), γ-butyrolactone (GBL), etc., all of which are high value-added chemical products.
[0003] The Repper synthesis method is currently the most widely used method for industrial production of BDO. This process uses acetylene and formaldehyde as raw materials. Under the action of a copper catalyst, 1,4-butynediol (BYD) is first synthesized, and BYD is then catalytically hydrogenated to obtain BDO. BYD hydrogenation to BDO is a series of reactions. First, BYD is hydrogenated to produce 1,4-butenediol (BED), and BED is then hydrogenated to produce BDO. The intermediate product BED in the hydrogenation process can be isomerized to produce γ-hydroxybutyraldehyde (γ-HALD), which will further hydrogenolyze to produce 2-butenol, n-butyraldehyde, n-butanol, etc. γ-HALD itself undergoes aldol condensation to produce long-chain byproducts and byproducts such as furan. Therefore, increasing the reaction rate of BED hydrogenation to produce BDO and reducing the accumulation of BED and γ-HALD in the reaction system can reduce the generation of byproducts.
[0004] At present, the catalytic hydrogenation of BYD to prepare BDO in industry is divided into two processes: two-stage hydrogenation and one-stage hydrogenation. Conventional powdered or granular Raney nickel catalysts are usually used in both hydrogenation processes. Since the solubility of H2 in BYD solution is very low, in order to ensure its complete hydrogenation and high selectivity conversion into BDO, a higher reaction temperature and extremely high reaction pressure are required. The reaction temperature of the Repper synthesis method is 120-150℃ and the pressure is as high as 25-35MPa. This process is short, but the reaction pressure is very high, resulting in large equipment investment. Therefore, the development of a catalyst with high hydrogenation activity under low pressure is of great significance to reducing process costs.
[0005] Patent CN101306368A discloses a method for preparing a second-stage hydrogenation catalyst for preparing butanediol by two-step hydrogenation of butynediol. The patent adopts an impregnation method to prepare a catalyst containing 5-25% nickel and 0.001-6% promoter. According to the examples, the reaction conditions are: temperature 120°C, reaction pressure 12MPa. The reaction temperature and pressure are still relatively high, and the BYD conversion rate is low, only about 80%.
[0006] Patent CN102744083B discloses a preparation and activation method of a special powder Raney nickel catalyst for the hydrogenation of BYD to BDO. When melting the nickel-aluminum metal alloy, 0.1-2 wt% of a modified metal X (X is Mg, B, Sr, Cr, S, Ti, La, Sn, W, Mo or Fe) is added, and the Ni-Al-X powder Raney nickel catalyst is prepared by the conventional activation treatment method of extracting with sodium hydroxide (NaOH) lye. The catalyst prepared by the method of extracting aluminum with lye in this patent has a relatively small specific surface area and a single pore structure, and the hydrogenation activity is relatively low, resulting in a relatively high concentration of the BYD hydrogenation intermediate BED (1,4-butenediol) in the reactor, thereby increasing side reactions. When the conversion rate of BYD is 98-100%, the selectivity of BDO < 95%, and a relatively large amount of butanol and acetal recombination components are generated.
[0007] In summary, it is necessary to develop a catalyst for the hydrogenation preparation of BDO, which can achieve high conversion rate and selectivity of BYD at lower reaction temperature and pressure, and is applied to the large-tonnage continuous BYD catalytic hydrogenation process. Summary of the Invention
[0008] The purpose of the present invention is to provide a fixed-bed hydrogenation catalyst, which is used for the reaction of hydrogenating 1,4-butynediol to 1,4-butanediol, and can achieve high selectivity of BDO and high conversion rate of BYD at a relatively low reaction pressure (5-10 MPa), reduce side reactions, lower production costs, and improve economic benefits.
[0009] To achieve the purpose of this invention, the following technical solutions are adopted:
[0010] First of all, the present invention provides a hydrogenation catalyst, which comprises an alloy core, a middle active layer and a surface hydrogen storage layer;
[0011] The composition of the alloy core is NixAlyMozFew, and the ratio of each element (mass ratio) is 40 ≤ x ≤ 60%, 30 ≤ y ≤ 58%, 1 ≤ z ≤ 5%, 1 ≤ w ≤ 5%; preferably, the particle size of the alloy core is 0.5-15 mm, preferably 1-8 mm;
[0012] The active layer is formed by activating and removing aluminum from the alloy core with an aqueous NaOH solution;
[0013] The composition of the hydrogen storage layer is TiaCrbVcNbdTae, and the ratio of each element (mass ratio) is 15 ≤ a ≤ 35%, 15 ≤ b ≤ 35%, 5 ≤ c ≤ 25%, 5 ≤ d ≤ 20%, 0 < e ≤ 20%; preferably, 20 ≤ a ≤ 35%, 20 ≤ b ≤ 25%, 10 ≤ c ≤ 25%, 5 ≤ d ≤ 15%, 10 < e ≤ 20%. Preferably, the thickness of the hydrogen storage layer is 1-10 μm.
[0014] The invention also relates to a method for preparing the catalyst.
[0015] A method for preparing a fixed bed hydrogenation catalyst comprises the following steps:
[0016] (1) Preparation of nickel-aluminum alloy particle core: Add metal Ni, metal Al and the third component Mo / Fe into a medium frequency melting furnace according to a ratio, and prepare an alloy with a specific formula by adjusting the frequency of the medium frequency melting furnace, controlling the appropriate current and heating time, and then prepare a nickel-aluminum alloy core after crushing, screening and surface shaping;
[0017] (2) Activation of alloy particles: using an alkaline solution (preferably a NaOH aqueous solution) to pass through the alloy particles at a certain flow rate for activation treatment; after the treatment is completed, the alkaline solution is switched to deionized water to wash the alloy particles until the pH value of the washed solution drops to 7-8, thereby preparing alloy particles having a porous nickel structure outer surface layer (middle active layer) and a dense structure inner core;
[0018] (3) Alloy particle pretreatment: The alloy particles are cleaned with acetone and / or ethanol and then vacuum dried; the surface of the substrate (the cleaned alloy particles) is bombarded with argon ions to sputter off the oxide layer on the surface of the substrate to prepare a catalyst substrate;
[0019] (4) Preparation of hydrogen storage alloy solid solution target: The target material is prepared in an arc melting furnace, and single metals V, Ti, Cr, Nb and Ta are added in proportion, and the arc gun is adjusted to the metal surface to strike the arc; after the arc is successfully struck, the arc gun is raised to the melting height, and the current of the arc gun is increased to melt, and the appropriate melting current and melting time are controlled, and the melting is repeated ≥ 4 times to prepare a hydrogen storage alloy solid solution as a target material;
[0020] (5) Hydrogen storage solid solution coating: The catalyst substrate prepared in step (3) and the target material prepared in step (4) are installed in a magnetron sputtering coating device, and the surface of the catalyst substrate is coated with a hydrogen storage solid solution to obtain a finished catalyst comprising an alloy core, a middle active layer and a surface hydrogen storage layer.
[0021] In step (1) of the present invention, the alloy core composition is Ni x Al y Mo z Fe w , wherein the ratio of each element is 40≤x≤60%, 30≤y≤58%, 1≤z≤5%, 1≤w≤5%.
[0022] The suitable current is 80-150A, and the heating time is 40-60min.
[0023] Preferably, the alloy is mechanically crushed and surface polished to prepare alloy particles with a particle size of 0.5 - 15 mm, preferably 1 - 8 mm.
[0024] In the present invention, the concentration of the NaOH solution in step (2) is 0.1 - 10 wt%, and the mass space velocity of the NaOH solution is 5 - 100 h -1 , the activation treatment temperature is 20 - 100 °C, and the activation treatment time is 1 - 8 h;
[0025] Preferably, the concentration of the NaOH solution is 0.5 - 5 wt%, and the weight space velocity of the NaOH solution is 10 - 50 h -1 , the activation treatment temperature is 20 - 80 °C, and the activation treatment time is 2 - 5 h.
[0026] In the present invention, the cleaning agent used in step (3) is acetone or ethanol, and it is used after vacuum drying after cleaning; the argon ion treatment process is as follows: start the mechanical pump to pump the magnetron sputtering chamber to a vacuum of 5 - 10 Pa, run the molecular pump, open the solenoid valve, and then pump to a high vacuum of <5×10 -4 Pa, introduce high-purity argon gas (99.999% Ar) into the sputtering chamber, the argon gas flow rate is 10 - 50 sccm, keep the chamber working pressure stable at 1.0 - 5.0 Pa, and treat the alloy particles.
[0027] In the present invention, the hydrogen storage layer composition in step (4) is Ti a Cr b V c Nb d Ta e , where the element ratios are 15 ≤ a ≤ 35%, 15 ≤ b ≤ 35%, 5 ≤ c ≤ 25%, 5 ≤ d ≤ 20%, 0 < e ≤ 20%. Preferably, 20 ≤ a ≤ 35%, 20 ≤ b ≤ 25%, 10 ≤ c ≤ 25%, 5 ≤ d ≤ 15%, 10 < e ≤ 20%.
[0028] The melting is carried out in an electric arc furnace. When the distance between the electric arc gun and the metal surface is adjusted to 2 - 3 mm, arc ignition is carried out; after successful arc ignition, raise the electric arc gun to the melting height for melting the hydrogen storage alloy solid solution;
[0029] Preferably, the melting height (distance between the electric arc gun and the metal surface) is 5 - 10 mm, the melting current is 150 - 200 A, the single melting time is 2 - 5 minutes, and the number of repeated melting times ≥ 4 times to ensure the uniformity of the sample composition.
[0030] As a preferred embodiment, the elemental V, the elemental Ti, the elemental Cr, the elemental Nb, and the elemental Ta are all single elements with a purity greater than 99.9%.
[0031] The hydrogen storage solid solution in step (5) of the present invention is coated in a magnetron sputtering coating device, the target sputtering power is set to 20W-100W, and the hydrogen storage solid solution is coated on the alloy surface.
[0032] Preferably, the solid solution coating has a thickness of 1-10 μm and a hydrogen storage density of >2.8 wt%.
[0033] The present invention further relates to the use of the catalyst.
[0034] The catalyst is used to catalyze the hydrogenation of unsaturated alcohol compounds to prepare saturated polyol compounds; preferably, the hydrogenation reaction is carried out in a fixed bed reactor, wherein the unsaturated alcohol compound is 1,4-butynediol, and the saturated polyol compound is 1,4-butanediol.
[0035] In a specific embodiment, the reaction conditions are: reaction temperature 120°C, reaction pressure 10.0 MPa, BYD feed mass space velocity 0.3 h -1 , hydrogen-to-oil ratio is 50: 1. The catalyst prepared by the invention can realize high-efficiency hydrogenation of 1,4-butynediol at high load in a fixed bed reactor.
[0036] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) Compared with the traditional Raney nickel catalyst, the hydrogenation catalyst of the present invention has better hydrogen absorption performance, greatly reduces the pressure required for the reaction, and has higher catalytic efficiency;
[0039] (2) The preparation method of the present invention can significantly improve the hydrogen absorption performance of the catalyst by coating the hydrogen storage solid solution alloy on the alloy surface, and can achieve high BYD conversion rate and selectivity at lower reaction temperature and pressure. It is applied to large-tonnage continuous BYD catalytic hydrogenation process, which is of great significance to reducing process costs. At the same time, the hydrogen storage layer has a strong bonding force with the catalyst alloy core, the catalyst has a long life, and good activity stability;
[0040] (3) The catalyst of the present invention has good hydrogen absorption performance, which solves the problem of slow hydrogenation rate in the reactor and high local BED concentration due to poor hydrogen dissolution effect of BYD aqueous solution, effectively inhibits the occurrence of side reactions, and the BDO selectivity can be ≥99.0%. At the same time, the BYD conversion rate is greater than 99.9%, which can meet the needs of large-tonnage continuous BDO production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a SEM image of the catalyst having a surface hydrogen-absorbing alloy layer structure prepared in Example 1 of the present invention.
[0042] The instrument used for catalyst morphology characterization is a scanning electron microscope (SEM), produced by Guoyi Quantum Corporation, model SEM5000X. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0044] Example 1
[0045] This embodiment provides a catalyst for BYD fixed bed hydrogenation and a preparation method thereof, wherein the preparation method comprises the following steps:
[0046] (1) 40.0 g of Ni metal, 58.0 g of Al metal, 1.0 g of Mo and 1.0 g of Fe were added into a medium frequency melting furnace, the medium frequency melting furnace (Beichen Yike DIH-160) was set to 50 Hz, the control current was 100 A, and the melting was heated for 40 min. After the melting was completed, the alloy liquid was poured into a cooling tank and cooled naturally to prepare a block alloy, and then after crushing, screening and surface shaping, a nickel-aluminum alloy core particle with a particle size of 3-6 mm was prepared;
[0047] (2) The alloy particles prepared in step (1) were loaded into a reaction tube, and the alloy particles were activated using a 1.0 wt% NaOH aqueous solution at a mass space velocity of 50 h -1 The alkali solution temperature is controlled at 60°C and the activation time is 5.0h through the alloy particle bed; after the activation is completed, the alkali solution is switched to deionized water to wash the alloy particles until the pH value at the outlet of the reaction tube is less than 8, thereby preparing alloy particles having a porous nickel structure outer surface layer and a dense structure inner core;
[0048] (3) The alloy particles prepared in step (2) were cleaned with 500 g of acetone and vacuum dried after cleaning; the mechanical pump was started to evacuate the magnetron sputtering chamber to a vacuum degree of 10 Pa, the molecular pump was operated, the solenoid valve was opened, and the high vacuum was then evacuated to a vacuum degree of <2×10 -4 Pa, high-purity argon gas (99.999% Ar) is introduced into the sputtering chamber with an argon flow rate of 50 sccm, and the chamber working pressure is kept stable at 1.0-5.0 Pa. Argon ions bombard the surface of the alloy particles and sputter off the oxide layer on the surface of the substrate to prepare a catalyst substrate.
[0049] (4) Add 35g of metal Ti, 15g of Cr, 25g of V, 5g of Nb and 20g of Ta into an arc melting furnace, adjust the distance between the arc gun and the metal surface to 2-3mm for arc striking; after the arc is successfully struck, raise the arc gun to 5mm from the metal surface, and increase the arc gun current to 180A. The single melting time is 2min, and the melting is repeated 4 times to prepare a hydrogen storage alloy solid solution as a target material.
[0050] (5) The catalyst substrate prepared in step (3) and the target material prepared in step (4) are installed in a magnetron sputtering coating device (nanoPVD S10A produced by Moorfield Nanotechnology), the target sputtering power is set to 20 W, and a hydrogen storage solid solution is coated on the surface of the alloy. The solid solution coating thickness is 5.0 μm, and a catalyst product comprising an alloy core, a middle active layer and a surface hydrogen storage layer is obtained. The hydrogen storage density of the surface hydrogen storage layer is 3.0 wt%, and the catalyst is numbered CAT-1.
[0051] The prepared catalyst was used to evaluate the performance of BYD hydrogenation to BDO, with a reaction temperature of 120 °C, a reaction pressure of 10.0 MPa, and a BYD feed mass space velocity of 0.3 h -1 , hydrogen-to-oil ratio of 50:1, continuous operation for 100 hours, sampling for gas chromatography analysis, BYD conversion rate reached 100%, selectivity for BDO was 99.2%, butanol production was 0.62%, and heavy component TBA production was 0.18%.
[0052] Example 2
[0053] This embodiment provides a catalyst for BYD fixed bed hydrogenation and a preparation method thereof. Except that the metal ratio in step (1) is adjusted to: 60.0 g metal Ni, 38.0 g metal Al, 1.0 g Mo and 1.0 g Fe, other conditions are the same as those in Example 1, and a catalyst numbered CAT-2 is prepared.
[0054] The performance of the CAT-2 catalyst for hydrogenation of BYD to BDO was evaluated under the same conditions as in Example 1. The catalyst was operated continuously for 100 hours, and samples were taken for gas chromatography analysis. The BYD conversion was 100%, the BDO selectivity was 98.8%, the butanol production was 0.9%, and the heavy component TBA production was 0.3%.
[0055] Example 3
[0056] This embodiment provides a catalyst for BYD fixed bed hydrogenation and a preparation method thereof, except that the concentration of the activated alkali solution in step (2) is adjusted to 5.0%, the mass space velocity of the alkali solution is adjusted to 10h -1, alkali solution temperature 80°C, activation time 2.0h, other conditions are the same as in Example 1, and a catalyst numbered CAT-3 is prepared.
[0057] The performance of the CAT-3 catalyst for hydrogenation of BYD to BDO was evaluated under the same conditions as in Example 1. The catalyst was operated continuously for 100 hours, and samples were taken for gas chromatography analysis. The BYD conversion was 100%, the BDO selectivity was 99.2%, the butanol production was 0.70%, and the heavy component TBA production was 0.10%.
[0058] Example 4
[0059] This embodiment provides a catalyst for BYD fixed bed hydrogenation and a preparation method thereof. Except that the metal ratio in step (4) is adjusted to: 20g metal Ti, 15g V, 35g Cr, 15g Nb and 15g Ta, other conditions are the same as those in Example 1, and a catalyst numbered CAT-4 is prepared.
[0060] The performance of the CAT-4 catalyst for hydrogenation of BYD to BDO was evaluated under the same conditions as in Example 1. The catalyst was operated continuously for 100 hours, and samples were taken for gas chromatography analysis. The BYD conversion was 99.8%, the BDO selectivity was 99.0%, the butanol production was 0.85%, and the heavy component TBA production was 0.15%.
[0061] Example 5
[0062] This embodiment provides a catalyst for BYD fixed bed hydrogenation and a preparation method thereof. Except that the target sputtering power in step (5) is adjusted to 50 W, a hydrogen storage solid solution is coated on the alloy surface with a solid solution coating thickness of 1.0 μm. Other conditions are the same as those in Example 1, and a catalyst numbered CAT-5 is prepared.
[0063] The performance of the CAT-5 catalyst for hydrogenation of BYD to BDO was evaluated under the same conditions as in Example 1. The catalyst was operated continuously for 100 hours, and samples were taken for gas chromatography analysis. The BYD conversion was 99.8%, the BDO selectivity was 98.7%, the butanol production was 0.93%, and the heavy component TBA production was 0.37%.
[0064] Comparative Example 1
[0065] This comparative example provides a catalyst for BYD fixed bed hydrogenation and a preparation method thereof. Except that step (4) and step (5) are not performed, other conditions are the same as those in Example 1.
[0066] The catalyst prepared in this comparative example was subjected to BYD hydrogenation to BDO performance evaluation under the same conditions as in Example 1. The catalyst was continuously operated for 100 hours, and samples were taken for gas chromatography analysis. The BYD conversion rate reached 98.5%, the selectivity to BDO was 95.2%, the butanol production was 3.7%, and the heavy component TBA production was 1.1%.
[0067] Comparative Example 2
[0068] This comparative example provides a catalyst for BYD fixed bed hydrogenation and a preparation method thereof. Except that the target material in step (4) is replaced with metal Ti and metal Ti is used to coat the alloy particles in step (5), other conditions are the same as those in Example 1.
[0069] The catalyst prepared in this comparative example was evaluated for its performance of hydrogenating BYD to produce BDO under the same conditions as in Example 1. The catalyst was operated continuously for 100 hours, and samples were taken for gas chromatography analysis. The BYD conversion rate reached 95.8%, the selectivity for BDO was 94.5%, the butanol production was 3.2%, and the heavy component TBA production was 2.3%.
[0070] Comparative Example 3
[0071] This comparative example provides a catalyst for BYD fixed bed hydrogenation and a preparation method thereof. Except that the alloy described in step (1) is replaced by 40.0 g of metal Ni and 60.0 g of metal Al for smelting preparation, other conditions are the same as those in Example 1.
[0072] The catalyst prepared in this comparative example was evaluated for its performance of hydrogenating BYD to produce BDO under the same conditions as in Example 1. The catalyst was operated continuously for 100 hours, and samples were taken for gas chromatography analysis. The results showed that the BYD conversion rate was 99.5%, the selectivity to BDO was 98.3%, the butanol production was 1.0%, and the heavy component TBA production was 0.7%.
[0073] Comparative Example 4
[0074] This comparative example uses 100.0 g of MC-507 commercial catalyst (purchased from EVONIK Company, brand: MC-507).
[0075] The performance of the catalyst of this comparative example in hydrogenating BYD to produce BDO was evaluated under the same conditions as in Example 1. The catalyst was operated continuously for 100 hours, and samples were taken for gas chromatography analysis. The BYD conversion was 99.5%, the selectivity to BDO was 95.2%, the butanol production was 3.0%, and the heavy component TBA production was 1.8%.
[0076] Comparative Example 5
[0077] This comparative example uses 100.0 g of Ni / Al2O3 commercial catalyst (purchased from Xunkai, brand: NiCAT-3000Q).
[0078] The performance of the catalyst of this comparative example in hydrogenating BYD to produce BDO was evaluated under the same conditions as in Example 1. The catalyst was operated continuously for 100 hours, and samples were taken for gas chromatography analysis. The BYD conversion rate reached 100%, the selectivity for BDO was 88.1%, the butanol production was 8.7%, and the heavy component TBA production was 3.2%.
[0079] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A hydrogenation catalyst, characterized in that The catalyst comprises an alloy core, a middle active layer and a surface hydrogen storage layer; The composition of the alloy core is NixAlyMozFew, where the mass percentage of each element is 40 ≤ x ≤ 60%, 30 ≤ y ≤ 58%, 1 ≤ z ≤ 5%, 1 ≤ w ≤ 5%; The active layer is formed by activating and removing aluminum from the alloy core with an aqueous NaOH solution; The composition of the hydrogen storage layer is TiaCrbVcNbdTae, where the mass percentage of each element is 15 ≤ a ≤ 35%, 15 ≤ b ≤ 35%, 5 ≤ c ≤ 25%, 5 ≤ d ≤ 20%, 0 < e ≤ 20%. Preferably, 20 ≤ a ≤ 35%, 20 ≤ b ≤ 25%, 10 ≤ c ≤ 25%, 5 ≤ d ≤ 15%, 10 < e ≤ 20%.
2. The catalyst according to claim 1, characterized in that The particle size of the alloy core is 0.5 - 15 mm, preferably 1 - 8 mm; and / or The thickness of the hydrogen storage layer is 1 - 10 μm.
3. The method for preparing the catalyst according to any one of claims 1 to 2, characterized in that: The preparation method includes: (1) Prepare nickel-aluminum alloy particles containing Mo / Fe; (2) Use an alkali solution to activate the alloy particles prepared in step (1), and wash them with deionized water to obtain alloy particles with a porous nickel-structured outer surface layer and a dense-structured core; (3) Dry the alloy particles obtained in step (2) under vacuum conditions, and use ion cleaning for pretreatment as a substrate; (4) In an arc furnace under vacuum conditions, melt metals V, Ti, Cr, Nb, and Ta multiple times to obtain a hydrogen storage alloy solid solution as a target; (5) Install the substrate and the target prepared in steps (3) and (4) in a magnetron sputtering coating device, and perform a hydrogen storage solid solution coating treatment on the surface of the alloy particles to prepare a catalyst product containing an alloy core, a middle active layer, and a surface hydrogen storage layer.
4. The method according to claim 3, characterized in that In step (1), add metals Ni, Al, and Mo / Fe according to the ratio into an intermediate frequency melting furnace, control the appropriate current and heating time by adjusting the frequency conversion of the intermediate frequency melting furnace, prepare an alloy, and then obtain a nickel-aluminum alloy core through crushing, screening, and surface shaping; preferably, the appropriate current is 80 - 150 A, and the heating time is 40 - 60 min.
5. The method according to claim 3, characterized in that: In the step (2), the alkaline solution is a NaOH solution with a concentration of 0.1-10 wt % and a mass space velocity of 5-100 h -1 , the activation treatment temperature is 20-100℃, and the activation treatment time is 1-8h; Preferably, the concentration of NaOH solution is 0.5-5wt%, and the weight space velocity of NaOH solution is 10-50h -1 The activation treatment temperature is 20-80℃ and the activation treatment time is 2-5h.
6. The method according to claim 3, characterized in that In step (3), clean the alloy particles with acetone and / or ethanol, and perform vacuum drying after cleaning; and / or The ion cleaning pretreatment process is as follows: start the mechanical pump to pump the magnetron sputtering chamber to a vacuum degree of 5-10Pa, run the molecular pump, open the solenoid valve, and then pump the high vacuum to <5×10 -4 Pa, high-purity argon gas is introduced into the sputtering chamber with an argon flow rate of 10-50 sccm, the chamber working pressure is kept stable at 1.0-5.0 Pa, the alloy particles are processed, and the oxide layer on the surface is sputtered off.
7. The method according to claim 3, characterized in that In step (4), the preparation of the target is carried out in an arc melting furnace, add elemental metals V, Ti, Cr, Nb, and Ta in proportion, and adjust the arc gun to the metal surface to strike an arc; After successful arc striking, raise the arc gun to the melting height, and at the same time increase the current of the arc gun for melting, control the appropriate melting current and melting time, and melt repeatedly ≥ 4 times to obtain a hydrogen storage alloy solid solution as a target; Preferably, strike an arc when the distance between the arc gun and the metal surface is adjusted to 2 - 3 mm; the melting height is 5 - 10 mm, the melting current is 150 - 200 A, and the melting time is 2 - 5 minutes.
8. The method according to claim 3, characterized in that In step (5), the sputtering power during the hydrogen storage layer coating process is 20 - 100 W.
9. Use of the catalyst according to any one of claims 1 to 8 for catalytic hydrogenation of unsaturated alcohol compounds to prepare saturated polyol compounds.
10. The use according to claim 9, characterized in that The unsaturated alcohol compound is 1,4-butynediol, and the saturated polyol compound is 1,4-butanediol.
Citation Information
Patent Citations
Preparation method of butanediol secondary hydrogenation catalyst by butynediol two-step hydrogenation
CN101306368A
Preparation and activation method of Raney nickel-aluminum-X catalyst for the hydrogenation of 1,4-butynediol to 1,4-butanediol
CN102744083B